Synthesis of porous MoCN polymer catalyst by ball-milling assisted thermal polycondensation and its preparation and application
Patent Information
- Application Number
- CN202611091558.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-20
AI Technical Summary
1、本发明采用球磨热缩聚将Mo以Mo-N6配位嵌入g-C3N4三嗪空腔并引入碳空位,使(002)峰偏移、比表面积升至41.35 m2/g、C/N比下降;Mo掺杂与碳空位使带隙缩至2.18 eV,抑制载流子复合、提升光电流2.6倍。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a catalyst for the degradation of antibiotics, specifically to a porous MoCN polymer catalyst synthesized by ball milling-assisted thermal polycondensation, and its preparation and application. Background Technology
[0002] Against the backdrop of rapid industrial development and sustained economic growth, large quantities of various antibiotics have entered the natural aquatic environment, causing serious harm to human health and the ecological environment. Developing efficient green wastewater purification technologies to treat antibiotic wastewater has become a global research hotspot. In the past, advanced oxidation technologies (AOPs) have been considered an effective means of removing organic pollutants from water. Among numerous technical pathways, heterogeneous photo-based Fenton reactions have attracted widespread attention due to their strong oxidizing power, ability to utilize unlimited solar energy, and controllable preparation, effectively overcoming the shortcomings of traditional homogeneous Fenton reactions, such as narrow pH application range and the formation of iron sludge. Compared with other commonly used oxidants and electron acceptors, persulfate (PDS) exhibits high storage stability, is easily oxidized, and is economical, with its O2O bond dissociation energy below 140 kJ·mol⁻¹. -1 (Persulfate PMS has a concentration of 377 kJ·mol⁻¹, and hydrogen peroxide (H₂O₂) has a concentration of 213 kJ·mol⁻¹), with a unit price of only $0.74 / kg (compared to $2.2 / kg for PMS and $1.5 / kg for H₂O₂). A key step in PDS activation is the migration of charge from the active site to the adsorbed PDS; therefore, the accumulation of electrons at the active sites is crucial for achieving efficient pollutant removal.
[0003] The performance of heterogeneous photo-Fenton technology ultimately depends on a highly efficient visible-light-responsive catalyst. Among various candidate materials, triazine polymers are ideal for solar-activated PDS due to their suitable band structure, strong chemical stability, and simple synthesis methods. However, their inherent defects—rapid recombination rate of photogenerated carriers and lack of specific active sites—severely limit their photocatalytic efficiency and restrict their practical application in the activation and degradation of organic pollutants by PDS. Cation doping, as a classic modification strategy, has been proven to effectively enhance the photocatalytic activity of semiconductors. The nitrogen sites containing lone pairs of electrons in the triazine polymer backbone provide unique advantages for the anchoring and coordination of metal ions. Molybdenum-doped materials are high-performance photocatalysts exhibiting excellent photochemical performance. Existing research shows that the introduction of molybdenum atoms into the nitrogen sites of triazine polymers forms a Mo-2C / 2N structure. Molybdenum doping regulates and optimizes the local electronic structure of the material, improving light absorption performance; simultaneously, molybdenum atoms, as active sites, enable the directional transfer of local charges, significantly promoting the separation of photogenerated carriers. Existing literature 1 (Taozhen Li, Xinyuan Wang, Zihao Fan, Xiaoning Wang, Zhuohang Wu, Muhammad Akram, Lei Wang, Juan Liu, Jingwen Pan, Baoyu Gao, Unique role of doped Mointo Fe-based catalyst to intensify peroxydisulfate activation for micropollutants degradation: Promote the conversion of SO4•- to FeIV=O, Chemical Engineering Journal, Volume 500, 2024, 157255, ISSN 1385-8947, https: / / doi.org / 10.1016 / j.cej.2024.157255) prepared FeMo@CN iron-molybdenum composite catalyst to activate peroxydisulfate for efficient degradation of bisphenol A. It can completely degrade bisphenol A in 1 hour, and the apparent rate constant is 129 times higher than that of the undoped molybdenum system, achieving stable and efficient degradation of bisphenol A. However, the activation of PDS in Reference 1 relies on only a single electron transfer path and has a single electron regulation method. It does not simultaneously introduce carbon vacancies to optimize the local electron distribution, and there is still considerable room for improvement in visible light capture and charge separation performance.Reference 2 (Zhang, L.; Wang, A.; Zhang, M.; Jin, Z.; Yi, H.; Wang, M. Effective Photocatalytic Hydrogen Evolution Using Covalent Triazine Framework-DerivedCarbon Nitride Nanofiber Containing Carbon Vacancies for Visible-Light-Driven. Appl. Sci. 2021, 11, 7222. https: / / doi.org / 10.3390 / app11167222) uses functionalized thiophene dicarboxylic acid and melamine as raw materials to pyrolyze a layered covalent triazine framework to obtain fibrous carbon nitride. A two-step calcination process is then used to construct carbon vacancies, which accelerates photogenerated charge transfer and enriches active sites. The visible light hydrogen evolution performance of this material is 66 times that of pure carbon nitride. However, Reference 2 only constructs carbon vacancies for photocatalytic hydrogen evolution, achieving only an improvement in hydrogen production performance, without coupling carbon vacancies with metal doping; it only explores the photocatalytic water splitting hydrogen production system, without extending to the persulfate-activated organic pollutant degradation scenario. Reference 3 (Lindong Liu, Qian Liu, Ying Wang, Jin Huang, Wenju Wang, Lian Duan, XiaoYang, Xiaoyong Yu, Xu Han, Nian Liu, Nonradical activation of peroxydisulfate promoted by oxygen vacancy-laden NiO for catalytic phenol oxidative polymerization, Applied Catalysis B: Environmental, Volume 254, 2019, Pages 166-173, ISSN 0926-3373, https: / / doi.org / 10.1016 / j.apcatb.2019.04.094) enhances the persulfate adsorption and activation capacity by introducing oxygen vacancies into nickel oxide to construct an electron-rich surface. Oxygen vacancies can lower adsorption energy and increase active sites, significantly improving the catalytic efficiency of phenol degradation. This system, through surface-activated complexes mediating the oxidative polymerization of phenol, can transform recalcitrant pollutants into high-value-added products.However, Reference 3 only introduces oxygen vacancies to activate PDS in NiO, resulting in weak visible light response of the metal oxide substrate and no broadening of light absorption by the conjugated framework of carbon triazine nitride. It relies solely on oxygen vacancies to regulate electrons without combining metal doping and carbon vacancies for dual modification, and is only suitable for phenol polymerization conversion. It lacks verification of the ability to degrade trace antibiotic pollutants. Summary of the Invention
[0004] The purpose of this invention is to provide a porous MoCN polymer catalyst synthesized by ball milling-assisted thermal polycondensation, as well as its preparation and application. This invention solves the problems of existing technologies, such as the single modification method and the lack of research on the synergistic degradation of antibiotics by molybdenum doping and carbon vacancies. In the reaction of antibiotic degradation by activated persulfate (PDS) under visible light, the reaction rate of this catalyst is 6.6 times that of the original triazine polymer (CN). The dual active sites formed by the doped molybdenum atoms and adjacent carbon vacancies synergistically construct a highly efficient "electron co-transfer" microenvironment.
[0005] To achieve the above objectives, the present invention provides a method for preparing porous MoCN polymer catalysts using a ball milling-assisted thermal polycondensation method, the method comprising: Ammonium molybdate tetrahydrate was mixed with melamine, ball-milled, calcined at 400 ℃~750 ℃, cooled to room temperature, and then ground into powder; the mass ratio of ammonium molybdate tetrahydrate to melamine was (10~70):5.
[0006] Preferably, the mass ratio of ammonium molybdate tetrahydrate to melamine is 50:5.
[0007] Preferably, the calcination temperature is 550 °C and the time is 180 min.
[0008] Preferably, the heating rate of the calcination is 5 °C·min. -1 .
[0009] The present invention provides a porous MoCN polymer catalyst prepared by the preparation method described above. The catalyst has a triazine polymer framework structure, and molybdenum is fixed in the cavity of the triazine polymer through Mo-N bond coordination. The (002) crystal plane diffraction peak of the catalyst shifts from 27.2° to 27.3° of CN, and the interlayer spacing is reduced.
[0010] Preferably, the Fourier transform infrared spectrum of the catalyst is at 418.5 cm⁻¹. -1 The characteristic absorption peak of the Mo-N bond appears at 3000 cm⁻¹, and at 3000 cm⁻¹. -1 ~3400 cm -1 The intensity of the –NH2 peak at that location is higher than that of pure g-C3N4.
[0011] Preferably, the catalyst has a specific surface area of 36.03~41.35 m². 2 ·g -1 The pore volume is 0.19~0.22 cm³. 3 ·g -1 The morphology exhibits a porous structure with curled edges and a hollow structure.
[0012] Preferably, the molybdenum element in the catalyst exists in a mixed valence state of Mo(VI) and Mo(V), and forms Mo-N6 and Mo-N5 coordination structures, respectively.
[0013] Preferably, the light absorption edge band of the catalyst is red-shifted to 477 nm, the band gap decreases to 2.18 eV, the conduction band potential is -0.56 V, and the valence band potential is 1.62 V; Or / and, the photocurrent response intensity of the catalyst under visible light irradiation is 2.6 times that of pure g-C3N4, and the charge transfer impedance is reduced to 1 / 7 of that of pure g-C3N4.
[0014] This invention provides the application of the porous MoCN polymer catalyst as described above in photocatalytic water splitting for hydrogen production and / or degradation of organic pollutants.
[0015] This invention utilizes the synergistic effect of vacancies and metal sites to achieve highly efficient activation of PDS in photo-Fenton-like degradation reactions. The synergistic construction of vacancies and metal sites provides more active sites for PDS adsorption. The dual active sites act as electron traps to achieve directional charge transfer, significantly promoting electron-hole separation and thus enhancing the activation effect of PDS. Using sulfamethoxazole (SMX) as the target antibiotic, this invention successfully designed and synthesized a molybdenum cation-doped triazine polymer (MoCN) rich in carbon vacancies under unadjusted pH conditions for PDS activation in highly efficient photo-Fenton-like degradation reactions. The degradation rate of sulfamethoxazole by MoCN is 6.6 times that of the original triazine polymer (CN). This superior performance stems from a significant increase in photoinduced electron concentration, enhanced charge carrier separation efficiency, and reduced electron transfer resistance in the material, ultimately achieving highly efficient PDS activation and rapid degradation of sulfamethoxazole. From the perspective of the reaction mechanism, the dual active sites formed by molybdenum atoms and adjacent carbon vacancies act as coupled electron traps, constructing an efficient "electron cooperative transfer" microenvironment. This structure enables the directional accumulation of electron density at the active sites, which greatly accelerates PDS activation and the subsequent generation of active free radicals, ultimately achieving broad-spectrum degradation of various antibiotics.
[0016] This invention discloses a porous MoCN polymer catalyst synthesized using a ball milling-assisted thermal polycondensation method, its preparation, and its application. This invention addresses the shortcomings of existing technologies, such as the limited modification methods and the lack of research on the synergistic degradation of antibiotics by molybdenum doping and carbon vacancies. It offers the following advantages: 1. This invention employs ball milling thermal polycondensation to embed Mo into the cavity of g-C3N4 triazine with Mo-N6 coordination and introduce carbon vacancies, thereby shifting the (002) peak and increasing the specific surface area to 41.35 m². 2 / g and C / N ratio decreased; Mo doping and carbon vacancies reduced the band gap to 2.18 eV, suppressed carrier recombination, and increased photocurrent by 2.6 times.
[0017] 2. In the visible light / PDS system, the degradation rate constant of the catalyst MoCN-50 of this invention for SMX is 6.6 times that of pure CN (82.6 × 10⁻⁶). -3 min -1 It removes 100% of antibiotics and achieves >85% removal after 5 cycles, exhibiting broad-spectrum and interference-resistant degradation capabilities against various antibiotics and actual water bodies. Attached Figure Description
[0018] Figure 1 The diagram shows the structural characterization results of the catalysts prepared in Example 1 and Comparative Example 1 of this invention.
[0019] Figure 2 The figures show the performance characterization results of the catalysts prepared in Example 1 and Comparative Example 1 of this invention.
[0020] Figure 3 The graph shows the degradation results of the catalysts prepared in Example 1 and Comparative Example 1 of this invention. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] The reagent information involved in the following examples is as follows: Melamine (C3H6N6), ammonium molybdate tetrahydrate ((NH4)6Mo7O) 24·4H2O), potassium persulfate (K2S2O8, PDS), sodium thiosulfate (Na2S2O3), norfloxacin (NOR), tetracycline (TC), sulfamethoxazole (SMX), acetonitrile (CH3CN), formic acid (HCOOH), methanol (CH3OH), ethanol (CH3CH2OH), 2,2,6,6-tetramethyl-4-piperidinol (TEMP), 2,2,6,6-tetramethylpiperidin nitroxide radical (TEMPO), and 5,5-dimethyl-1-pyrrolidone-N-oxide (DMPO) were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; levofloxacin hydrochloride (Levo-HCl) and ciprofloxacin (CIP) were purchased from Beijing Innocare Technology Co., Ltd.
[0023] This invention utilizes the Vienna Ab initio Simulation software package (VASP) for density functional theory (DFT) calculations. It employs the Perdew-Burke-Ernzerhof (PBE) functional under the generalized gradient approximation (GGA) to describe exchange-correlation effects, and selects the projected fused wave (PAW) method to simulate the ion core, setting the cutoff energy to 450 eV. The DFT-D3 empirical correction method is used to describe van der Waals interactions. The force convergence threshold for geometric optimization is less than 0.02 eV·Å. -1 The electronic convergence limit is set to 1×10. -5 eV, the Brillouin zone was sampled using a 2×2×1 Monkhorst-Pack k-point grid. After full geometry optimization, a 4×4×1 Monkhorst-Pack k-point grid was used to calculate the electronic localization function (ELF), Bader charge, and projected density of states (PDOS).
[0024] Example 1 A method for synthesizing porous MoCN polymer catalysts using ball milling-assisted thermal polycondensation, the method comprising: 10 mg, 30 mg, 50 mg, or 70 mg of ammonium molybdate tetrahydrate were each mixed with 5 g of melamine and ball-milled for 60 min until homogeneous. The resulting precursor mixtures were then placed in a muffle furnace and milled at 5 ℃·min. -1 The temperature was increased to 550℃ and calcined for 180 min. After cooling to room temperature, the residual gray solid was ground into powder and successively labeled as MoCN-10, MoCN-30, MoCN-50 or MoCN-70.
[0025] Comparative Example 1 A method for synthesizing CN catalysts using ball milling-assisted thermal polycondensation is basically the same as that in Example 1, except that: The original CN material was prepared by directly calcining 5 g of melamine using the same thermal polymerization method, and is denoted as CN.
[0026] Experimental Example 1: Material Characterization The chemical composition and crystal structure of the catalysts in Example 1 and Comparative Example 1 were analyzed using a Malvern Panaco Aeris X-ray diffractometer (Cu Kα, λ=1.54178 Å). The surface morphology of the materials was observed using a Thermo Fisher Scientific Prisma E field emission scanning electron microscope (FESEM), and transmission electron microscopy (TEM) images were obtained using a FEI Talos F200X G2 transmission electron microscope (accelerating voltage 200 kV), with elemental analysis performed using the super X-ray energy dispersive X-ray spectrometer (EDX) equipped with the instrument. The Fourier transform infrared (FTIR) spectra of the samples were determined using a Bruker Invenio R Fourier transform infrared spectrometer by the KBr pellet method. The surface elemental composition and chemical state of the materials were analyzed using a Thermo Fisher Scientific X-ray photoelectron spectrometer (Al Kα monochromatic light source).
[0027] like Figure 1 The figures shown are structural characterization results of the catalysts prepared in Example 1 and Comparative Example 1 of this invention, where a) is a schematic diagram of the synthesis process of the MoCN catalyst; b) is the XRD pattern of different samples; c) is the SEM image of MoCN-50; d) is the TEM image of MoCN-50; e) is the X-ray energy dispersive spectroscopy elemental distribution map of MoCN-50; f) is the C 1s high-resolution XPS pattern of CN and MoCN-50; g) is the N 1s high-resolution XPS pattern of CN and MoCN-50; h) is the Mo 3d high-resolution XPS pattern of CN and MoCN-50. Figure 1 As can be seen from a), in the process of synthesizing porous MoCN photocatalysts using the ball milling-assisted thermal polycondensation method of the present invention, the negatively charged Mo7O 24 6- Polyanionic polymers and melamine precursors were thoroughly mixed by ball milling; subsequently, a molybdenum-containing intermediate was calcined in air at 823 K, followed by high-temperature thermal condensation to form a grayish-brown triazine polymer. Figure 1b) XRD patterns show that all samples exhibit two characteristic diffraction peaks at 2θ≈12.7° and 27.3°, corresponding to the (100) and (002) crystal planes of typical graphitic carbon nitride (g-C3N4), respectively, originating from its in-plane ordered structure and interlayer periodic stacking. With the introduction of molybdate, the intensity of the two characteristic peaks gradually decreases, indicating that the long-range ordered structure of CN is disrupted to some extent. Notably, the (002) diffraction peak of MoCN-50 shifts from 27.2° to 27.3° of CN, moving towards a higher angle, indicating that the introduction of exogenous molybdenum species reduces the interlayer spacing of the material, a change that may facilitate charge migration between layers and in space. No characteristic peaks of molybdenum oxides / nitrides were detected in the patterns. This is because the ionic radius and electronic configuration of molybdenum differ significantly from those of the host lattice, making it impossible for molybdenum to substitute carbon and nitrogen sites equivalently or non-equivalently in aromatic heterocycles. The above results indicate that there is a strong electrostatic interaction between the positively charged molybdenum species and the nitrogen site containing lone pairs of electrons, which may allow molybdenum atoms to be fixed in the two-dimensional triazine cavity of g-C3N4 through Mo-N coordination. This process leads to the loss of sp2 hybrid carbon atoms, generating more –NH2 groups, and at the same time, carbon vacancies (Cv) are formed during the synthesis process.
[0028] The surface morphology and microstructure of the samples were observed using field emission scanning electron microscopy and high-resolution transmission electron microscopy. After the introduction of molybdenum species, numerous pores formed on the MoCN-50 surface. This is likely due to the large amounts of gas (such as NH3 and CO2) generated by the thermal decomposition of nitrogen-rich precursors and polymolybdates, creating a gas template effect. Interestingly, the Mo-N coordination in the trihomocysteine framework caused edge curling in the planar layers of the material, partially transforming it into a hollow structure. Figure 1 The EDX element mapping image of (e) confirms that C, N, and Mo elements are spatially uniformly distributed in MoCN-50.
[0029] XPS analysis of the surface elemental composition and chemical state of the samples revealed that after molybdenum doping, the surface C / N atomic ratio of MoCN-50 decreased from 0.762 for CN to 0.727, indicating the loss of carbon species from the aromatic framework of MoCN-50 and the possible formation of carbon vacancies. Figure 1As shown in f), the three characteristic peaks of pure CN at 284.8 eV, 286.6 eV, and 288.3 eV correspond to amorphous impurity carbon (CC), C-NHx, and NC=N, respectively. However, in MoCN-50, the binding energy of NC=N shifts negatively to 288.1 eV, and the peak area ratio of C-NHx / NC=N increases from 0.06 for CN to 0.11. This indicates that the NC=N structure in the triazine ring is disrupted, generating more edge C-NHx groups. Simultaneously, the coordinated nitrogen atom transfers excess electrons to the sp2 hybridized carbon atom in NC=N. Figure 1 As shown in g), the peaks at 398.7 eV, 399.8 eV, 401.2 eV, and 404.5 eV for pure CN correspond to CN=C, N-C3, NHx, and π excitations, respectively. A new peak appears at 397.0 eV in MoCN-50, confirming the formation of Mo-N bonds in the matrix, and the peak area ratio of π excitation decreases from 5.5% for CN to 4.6%. These results indicate that the planar conjugated structure of the material is somewhat disrupted, with nitrogen atoms (CN=C and N-C3) donating electrons to adjacent atoms, leading to a decrease in the polarizability of MoCN-50. Simultaneously, the introduction of molybdenum causes partial occupation of the antibonding π orbitals of CN. Figure 1 As shown in h), the peaks can be divided into three sets of characteristic peaks: the peaks at 232.5 eV and 235.6 eV confirm the presence of the Mo(VI) species, and the characteristic peaks at 229.9 eV and 233.0 eV correspond to Mo-N bonds. Clearly, the positively charged molybdenum cation successfully embeds itself into the two-dimensional triazine cavity by binding with six nitrogen sites containing lone pairs of electrons, resulting in a unique Mo-N6 coordination structure for the MoCN-50 catalyst. Furthermore, characteristic peaks of Mo(V) at 231.4 eV and 234.5 eV were detected, which may be due to the increase in carbon vacancies and terminal N-Hx groups, leading to the formation of a Mo-N5 conjugated coordination structure for some molybdenum atoms. Combining the FTIR and XRD results, it can be inferred that exogenous molybdenum atoms are incorporated into the nitrogen-rich aromatic network of g-C3N4 via nitrogen bridging.
[0030] This invention uses barium sulfate as a reference and measures the UV-Vis diffuse reflectance (UV-Vis DRS) spectrum of the sample using a Shimadzu UV-2700 UV-Vis spectrophotometer; at an excitation wavelength of 380 nm, the photoluminescence (PL) spectrum is measured using an Agilent CaryEclipse fluorescence spectrophotometer; at an excitation wavelength of 430 nm, the time-resolved photoluminescence (TRPL) spectrum is measured using an Edinburgh FLS1000 fluorescence spectrometer; and at 293 K, electron paramagnetic resonance (EPR) is performed using a paramagnetic technology EPR200M electron paramagnetic resonance spectrometer. Solid sample vacancy detection parameters: central magnetic field 3495 G, scan width 2000 G, resolution 2000 points, scan time 100 s; DMPO, TEMP, and TEMPO were used as spin traps to detect free radicals and photogenerated holes in suspensions, with the following parameters: central magnetic field 3500 G, scan width 100 G, resolution 1024 points. The instantaneous photocurrent curve, Mott-Schottky curve, and electrochemical impedance spectroscopy (EIS) of the samples were determined using a Chenhua CHI 618C electrochemical workstation with a standard three-electrode system. A platinum sheet was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. The electrochemical impedance spectroscopy (EIS) was performed at 0.5 mol·L⁻¹. -1 Sodium sulfate aqueous solution was used as the electrolyte. Working electrode preparation: 6.0 mg of the powder sample was uniformly dispersed in 3 mL of 0.5 wt% Nafion ethanol solution. The suspension was coated onto a fluorine-doped tin oxide (FTO) conductive glass plate with an effective area of 1.0 cm² and air-dried at room temperature. Instantaneous photocurrent curves were measured at a bias voltage of 0.4 V (relative to the standard hydrogen electrode NHE); electrochemical impedance spectroscopy was measured at -0.6 V (relative to NHE), with an AC frequency range of 0.01 Hz to 10000 Hz.
[0031] like Figure 2 As shown, the performance characterization results of the catalysts prepared in Example 1 and Comparative Example 1 of this invention are illustrated, where a) is an inset of UV-Vis diffuse reflectance spectra (inset: corresponding Tauc plot); b) is an in-situ solid-state electron paramagnetic resonance spectrum; c) is a steady-state photoluminescence spectrum; d) is a time-resolved photoluminescence spectrum; e) is an instantaneous photocurrent response curve; and f) is an electrochemical impedance spectroscopy Nyquist plot. Figure 2As shown in a), the introduction of molybdenum and carbon vacancies effectively modulates the light absorption performance and electronic structure of pure CN: compared with pure CN, the light-harvesting ability of MoCN-50 is significantly improved, especially in the visible light region of 430~800 nm. This improvement is due to the enhancement of n→π* electronic transition. At the same time, the absorption edge of the material redshifts from 461 nm in CN to 477 nm. This may be due to the formation of carbon vacancy-related impurity bands, which promotes the excitation process of photoelectrons from the defect state to the guide band (CB).
[0032] Based on the Tauc plot, the band gap energy (Eg) of MoCN-50 is calculated to be 2.18 eV, which is much smaller than the 2.54 eV of pure CN. The valence band (VB) and conduction band (CB) potentials of the sample are calculated using the following formula: EVB = φ + VB max -4.44 eV (1); E g =E VB -E CB (2); In equations (2) and (3), EVB is the valence band potential relative to the standard hydrogen electrode (NHE), ECB is the conduction band potential relative to NHE, Φ is the electron work function of the analyzer (4.2 eV), and VB max The maximum valence band value obtained from the XPS valence band spectrum is given. The calculated EVB and ECB of CN are 1.85 V and -0.69 V, respectively, while the EVB and ECB of MoCN-50 are tuned to 1.62 V and -0.56 V. The strong Mo-N interaction and the formation of carbon vacancies narrow the band gap of MoCN-50 and make its energy levels suitable, which not only benefits visible light absorption but also provides thermodynamic advantages for photodegradation reactions.
[0033] Carbon vacancies facilitate charge separation and oxygen activation; therefore, the carbon vacancies in the catalyst were characterized by EPR testing (Figure 2b): both samples exhibited Lorentz lines with a g value of 2.003 in a magnetic field range of 3450–3550 G, confirming the presence of carbon vacancies. However, compared to pure CN, MoCN showed a higher spin signal intensity, indicating a greater carbon vacancy concentration. This is due to the loss of carbon atoms from the CN heterocycle, resulting in increased spin density around the carbon vacancies. 2Hybridized nitrogen atoms generate unpaired electrons. The signal from MoCN-50 is stronger, indicating an increased carbon vacancy concentration. Furthermore, a signal with a g-value of 1.991 was detected in the molybdenum-doped sample, corresponding to the Mo(V) species, consistent with XPS results. Previous literature reports that defects can suppress photogenerated carrier recombination by trapping electrons, thereby promoting the generation of active radicals in catalytic reactions. The enhanced signal intensity of carbon vacancies under illumination indicates an increase in unpaired electron density, confirming that carbon vacancies can trap photogenerated electrons; moreover, the signal intensity change of MoCN-50 is greater than that of CN, stemming from its higher carbon vacancy concentration, fully demonstrating the charge-trapping effect of carbon vacancies, thus significantly improving charge carrier separation efficiency. Figure 2 As shown in c), at an excitation wavelength of 380 nm, pure CN exhibits the highest PL intensity due to the delocalization characteristics of its conjugated structure; while the PL intensity of MoCN is significantly reduced, with MoCN-50 showing the lowest signal intensity. This indicates that the efficient electron trapping effect of molybdenum atoms and carbon vacancies significantly suppresses charge carrier recombination; simultaneously, influenced by carbon vacancies, the emission peak of the material blue-shifts from 430 nm to 427 nm. Figure 2 As shown in d), molybdenum doping shortens the lifetime of photoexcited electrons from 4.72 ns to 3.92 ns, indicating that photogenerated electrons achieve rapid and efficient migration. Figure 2 e) Instantaneous photocurrent curve and Figure 2 f) Electrochemical impedance spectroscopy results show that the photocurrent response of MoCN-50 is approximately 2.6 times that of pure CN, and the electron transfer resistance is reduced to about 1 / 7 of that of CN. Based on the above analysis, it can be inferred that molybdenum atoms and carbon vacancy sites synergistically construct an "electron co-transfer" microenvironment, ultimately achieving an increase in photoinduced carrier concentration and accelerated charge migration and separation.
[0034] Experiment Example 2 verifies degradation performance Using visible light (400≤λ≤800 nm) as the light source and PDS as the activator, the degradation performance of the catalysts prepared in Example 1 and Comparative Example 1 on various antibiotic pollutants was investigated. Specific procedure: 25 mg of catalyst was dispersed in 50 mL of a 5 mg·L⁻¹ solution. -1 The contaminant solution (including SMX, TC, Levo-HCl, NOR, and CIP) was magnetically stirred for 30 min in the dark to reach adsorption-desorption equilibrium. Subsequently, the suspension was irradiated under a 100 W LED light source (PLS-LED 100C) equipped with a filter, and 40 mg of PDS was added simultaneously. At different reaction times, 2 mL samples were taken, filtered through a polyethersulfone (PES) membrane, and immediately 30 μL of a 2 mol·L⁻¹ solution was added.-1 The reaction was quenched with sodium thiosulfate solution and then analyzed. Throughout the photo-Fenton reaction, the reaction temperature was controlled at 25 °C using a circulating water cooling system. The concentration of organic pollutants was determined using a high-performance liquid chromatograph (Shimadzu, LC-2030 Plus) with a C18 column (5 μm, 4.6 × 250 mm). The degradation rate of the catalyst was calculated using the following formula: -ln(C t / C0)=kt (3; In equation (1), C t C0 represents the instantaneous concentration of antibiotic contaminants during the degradation process, C0 represents the initial concentration of antibiotic contaminants, k represents the reaction rate constant, and t represents the reaction time.
[0035] Furthermore, the stability and reusability of the catalyst in photo-induced Fenton reactions were investigated through cyclic experiments. After each cycle, the catalyst was recovered by filtration and treated with 0.1 mol·L⁻¹. -1 Wash with alternating nitric acid and ultrapure water for the next experiment.
[0036] like Figure 3 The figure shows the degradation results of the catalysts prepared in Example 1 and Comparative Example 1 of this invention, where a) is the degradation efficiency of sulfamethoxazole under different control conditions; b) is the degradation efficiency of sulfamethoxazole at different pH values; c) is the effect of coexisting ions on the removal of sulfamethoxazole; d) is the degradation performance of sulfamethoxazole in actual water bodies; and e) is the degradation effect of the catalyst on various antibiotics. (Reaction conditions: catalyst concentration 0.5 g·L⁻¹) -1 PDS concentration 0.8 g·L -1 Initial antibiotic concentration 5 mg·L -1 f) represents the degradation efficiency of the catalyst for micropollutants (reaction conditions: catalyst concentration 0.1 g·L⁻¹). -1 PDS concentration 0.1 g·L -1 Initial antibiotic concentration 1 mg·L -1 ).Depend on Figure 3 As shown in section a), using visible light (λ≥420 nm) as the light source, PDS as the activator, and sulfamethoxazole (SMX) as the probe antibiotic, the degradation performance of the synthesized catalysts was investigated. The adsorption rate of sulfamethoxazole for all tested samples was less than 10%; the removal rate of sulfamethoxazole in the CN / PDS / visible light system was only 54.2%, while the removal rates of all MoCN samples were significantly increased to 92.5%–100%, highlighting the important role of molybdenum and carbon vacancy functionalization in enhancing catalytic activity. Among them, the optimal sample, MoCN-50, had a degradation rate constant k of 82.6 × 10⁻⁶. -3 min -1Approximately 12.5 × 10⁻⁶ pure CN. -3 min -1 The removal rate of sulfamethoxazole was 6.6 times that of other drugs, therefore MoCN-50 was selected as the model catalyst for further research. Control experiments showed that MoCN-50 alone, or the MoCN-50 / PDS and PDS / visible light systems, were insufficient for removing sulfamethoxazole; the MoCN-50 / visible light system slightly improved the removal rate of sulfamethoxazole to 41.3%, with a k value of 7.0 × 10⁻⁶. -3 min -1 This demonstrates the inherent photocatalytic performance of MoCN-50; while the MoCN-50 / PDS / visible light system exhibits excellent catalytic degradation performance, achieving a 100% removal rate of sulfamethoxazole with a k value of 82.6 × 10⁻⁶. -3 min -1 This indicates that light irradiation is crucial for enhancing MoCN-50-mediated PDS activation and achieving sulfamethoxazole degradation. These results confirm that the synergistic effect of MoCN-50, PDS, and visible light is key to achieving efficient sulfamethoxazole removal, and this synergistic effect may stem from the efficient activation of PDS by photogenerated electrons on MoCN-50.
[0037] The relevant reaction equations for PDS activation are as follows: (4) and (5): S2O8 2- + H + → HS2O8 - (4); HS2O8 - + e - → SO4•- + SO4 2- + H + (5); Depend on Figure 3 As shown in b), MoCN-50's high activation efficiency for PDS allows it to exhibit excellent resistance to pH changes within a pH range of 3.0 to 7.0. However, when the pH is 9.0, the degradation efficiency decreases slightly (87.13%), mainly due to two reasons: firstly, according to reaction formulas (4) and (5), PDS is more easily activated in acidic media; secondly, high concentrations of OH... - Hydroxyl radicals (·OH) will be generated on the catalyst surface, inhibiting the charge transfer process between adsorbed PDS and sulfamethoxazole molecules. Figure 3 From c), it can be seen that even if 5 mmol·L⁻¹ is added to the system... -1 Anions and cations (Ca) 2+ Na + Mg 2+ NO3- Cl - SO4 2- After 60 minutes of illumination, the removal rate of sulfamethoxazole remained above 97.7%. The degradation efficiency showed no significant change under high ionic strength, indicating that the catalytic system has excellent resistance to interference from coexisting substances. Figure 3 As shown in d), the degradation efficiency of sulfamethoxazole in tap water and river water in Chengdu only decreased slightly (the decrease was less than 2%); even in domestic sewage containing a large number of microorganisms and other organic matter, the removal rate of sulfamethoxazole was still as high as 93.7%, indicating that this advanced oxidation system has good application prospects in various actual water bodies. Figure 3 As shown in e), the broad-spectrum photodegradation of various organic pollutants by MoCN-50, including tetracycline (TC), levofloxacin hydrochloride (Levo-HCl), norfloxacin (NOR), and ciprofloxacin (CIP), was investigated, and the results showed that all tested pollutants could be completely degraded. Figure 3 From f), it can be seen that under low concentration conditions (catalyst 0.1 g·L), -1 PDS 0.1 g·L -1 Antibiotics 1 mg / L -1 The system still exhibits good degradation effects on micro-pollutants: sulfamethoxazole and tetracycline can be completely degraded, and the degradation rates of levofloxacin hydrochloride, norfloxacin, and ciprofloxacin reach 95.5%, 75.6%, and 81.8%, respectively, confirming that the catalyst has excellent degradation performance for wastewater containing micro-pollutants.
[0038] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.
Claims
1. A method for preparing porous MoCN polymer catalysts using ball milling-assisted thermal polycondensation, characterized in that, The method includes: Ammonium molybdate tetrahydrate was mixed with melamine, ball-milled, calcined at 400 ℃~750 ℃, cooled to room temperature, and then ground into powder. The mass ratio of ammonium molybdate tetrahydrate to melamine is (10~70):
5.
2. The preparation method according to claim 1, characterized in that, The mass ratio of ammonium molybdate tetrahydrate to melamine is 50:
5.
3. The preparation method according to claim 1, characterized in that, The calcination temperature was 550 ℃ and the time was 180 min.
4. The preparation method according to claim 3, characterized in that, The heating rate for calcination is 5 °C·min. -1 .
5. A porous MoCN polymer catalyst prepared by the method according to any one of claims 1 to 4, characterized in that, The catalyst has a triazine polymer framework structure, and molybdenum is fixed in the cavity of the triazine polymer through Mo-N bond coordination; the (002) crystal plane diffraction peak of the catalyst shifts from 27.2° to 27.3° of CN, and the interlayer spacing decreases.
6. The porous MoCN polymer catalyst according to claim 5, characterized in that, The Fourier transform infrared spectrum of the catalyst is at 418.5 cm⁻¹. -1 The characteristic absorption peak of the Mo-N bond appears at 3000 cm⁻¹, and at 3000 cm⁻¹. -1 ~3400 cm -1 The intensity of the –NH2 peak at that location is higher than that of pure g-C3N4.
7. The porous MoCN polymer catalyst according to claim 5, characterized in that, The catalyst has a specific surface area of 36.03~41.35 m². 2 ·g -1 The pore volume is 0.19~0.22 cm. 3 ·g -1 The morphology exhibits a porous structure with curled edges and a hollow structure.
8. The porous MoCN polymer catalyst according to claim 5, characterized in that, In the catalyst, molybdenum exists in a mixed valence state of Mo(VI) and Mo(V), and forms Mo-N6 and Mo-N5 coordination structures, respectively.
9. The porous MoCN polymer catalyst according to claim 5, characterized in that, The catalyst exhibits a red shift of the light absorption edge band to 477 nm, a band gap reduced to 2.18 eV, a conduction band potential of -0.56 V, and a valence band potential of 1.62 V. Or / and, the photocurrent response intensity of the catalyst under visible light irradiation is 2.6 times that of pure g-C3N4, and the charge transfer impedance is reduced to 1 / 7 of that of pure g-C3N4.
10. The application of a porous MoCN polymer catalyst as described in any one of claims 5 to 9 in photocatalytic water splitting for hydrogen production and / or degradation of organic pollutants.